PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS KINEMASTER MATERI AKU DAN CITA-CITAKU - Nelin Nur Agustin; Ana Nurhasanah; M. Taufik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The goal of this study is to develop kinemaster-based audio-visual media. This study uses Research and Development (RnD) with 4D model (Define, Design, Development, Desseminate). The subjects were 38 students of class IV B SDN Kramatwatu 1. The data were collected through observation, interviews, and questionnaires. Data analysis carried out is qualitative and quantitative. The results of the study obtained an average value of expert validation with a percentage of 88.6% which was included in the very feasible category, the average value of student respondents obtained a percentage of 92.7% which was included in the very feasible category. Thus, it can be concluded that kinemaster-based audio-visual media can be used in learning and is worthy of being used as learning media.